Non-Contrast Radiation Free NIR Lung Imaging - Votruba, Jiří; Drahanský, Martin; Goldmann, Tomáš; Brůha, Tomáš; Kolář, Radim (MDPI, 2025)
Background/Objectives: Early localization of solitary pulmonary nodules (SPNs) remains challenging despite technological advances in endoscopic navigation, as the procedure often necessitates multiple ionizing imaging examinations. This study aimed to develop and evaluate a radiation-free optical method for SPN localization based on near-infrared (NIR) translumination. Methods: A miniaturized NIR light source was introduced into the bronchial tree to illuminate the lung parenchyma. The transmitted and scattered NIR light was detected in real time from the pleural side using minipleuroscopy and a CMOS camera. The approach exploits intrinsic differences in optical absorption and scattering between normal and pathological lung tissue, allowing visualization of the parenchymal micro-architecture without exogenous contrast agents. Results: In ex vivo porcine lungs, tissue structures were clearly visualized through up to approximately 4 cm of parenchyma. In a ventilated pig (n = 1), bronchial NIR illumination was consistently detected from the pleural cavity and produced distinct images of lobular structures and the bronchial mucosa. Conclusions: These feasibility findings demonstrate that NIR translumination can provide radiation-free intra-thoracic visualization and may serve as a valuable adjunct for biopsy guidance. Further quantitative validation and clinical translation are warranted to establish its applicability in human pulmonary procedures.
Keywords: solitary pulmonary nodule; NIR; lung imaging; translumination